тан і розвиток культури доби сучасної незалежної Української держави (1991-2008 рр.) (Zaporizhzhia Historical Review, 2021)
The article deals with the culture in the independent Ukrainian state in 1991-2008. The analysis of the state and development of the culture is given in the article. The main attention is drawn to the phenomena and processes taking place in the fields of education, science, literature, art, publishing and sport.